The idea of God in early religions - Jevons, F. B. (Frank Byron), 1858-1936. (Cambridge, University Press, 1910)
Includes brief references to the religious beliefs and practices of Aboriginal Australians.
Bibliography: p. [ix]-x.
Keywords: Religion; God; Religion - Theory and criticism